Styles of policing and economic development in African states - Marenin, Otwin (2014)
The notion that economic development in African states requires minimal levels of security has become widely accepted in the international development community. The question is which types of security provision---professional all service policing or functionally specialized agencies---will have the greater impact on promoting and sustaining economic development. Using mainly available data and analyses by van Dijk, I argue that functional policing styles and work are more important to address the major obstacle to economic development: grand corruption, organized crime, political violence, fraud and mismanagement by government than professional all-service policing. - Reproduced.
Keywords: Police - Africa; Economic and social development - Africa; Police